FACTORS AIMED AT DEVELOPING COMPETENCIES IN PHYSICS EDUCATION - N.Z.Mamadaliyeva (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: intensive work on improving physics education, the goals and objectives of physics teaching are presented.